Factors affecting the retention of reserve officer training corps students at the University of Wisconsin - La Crosse - Powell, Robert Lee (My University, 1974)
The problem of this study was to determine what factors influence Reserve Officer Training Corps students to drop out of the program at UW-LaCrosse after the initial semester and also to determine significant factors causing other students to continue in the program.
Keywords: United States. Army. Reserve Officers? Training Corps; University of Wisconsin - La Crosse. Military Science Dept.; Military education -- Wisconsin -- La Crosse; Armed Forces -- Officers -- Training of